2017
DOI: 10.1109/tnb.2017.2718967
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz Channel Model and Link Budget Analysis for Intrabody Nanoscale Communication

Abstract: Nanosized devices operating inside the human body open up new prospects in the healthcare domain. Invivo wireless nanosensor networks (iWNSNs) will result in a plethora of applications ranging from intrabody health-monitoring to drug-delivery systems. With the development of miniature plasmonic signal sources, antennas, and detectors, wireless communications among intrabody nanodevices will expectedly be enabled at both the terahertz band (0.1-10 THz) as well as optical frequencies (400-750 THz). This result m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(60 citation statements)
references
References 53 publications
2
58
0
Order By: Relevance
“…Several works exist pointing to the THz band as an enabler of in-vivo wireless nanosensor networks (iWNSNs) [194] [195]. In particular, the authors in [196] presented an attenuation model of intrabody THz propagation to facilitate the accurate design and practical deployment of iWNSNs. In subsequent studies, the authors also demonstrated both the photothermal impact [197] along with the noise effect [198] of THz intrabody communication to further verify the feasibility and prosperity of such propagation mechanism.…”
Section: A Terahertz Nanoscale Applicationsmentioning
confidence: 99%
“…Several works exist pointing to the THz band as an enabler of in-vivo wireless nanosensor networks (iWNSNs) [194] [195]. In particular, the authors in [196] presented an attenuation model of intrabody THz propagation to facilitate the accurate design and practical deployment of iWNSNs. In subsequent studies, the authors also demonstrated both the photothermal impact [197] along with the noise effect [198] of THz intrabody communication to further verify the feasibility and prosperity of such propagation mechanism.…”
Section: A Terahertz Nanoscale Applicationsmentioning
confidence: 99%
“…Research in this field mainly focuses on the study of the terahertz band as well as the investigation of new nanoantennas based on nanomaterials [208]. The miniaturization of a conventional antenna to meet the size requirements of a nanosensor results in very high resonance frequencies, in the order of several hundred terahertz [209]. One of the applications of intrabody nanonetworks has been the monitoring of the human nervous system.…”
Section: Ibc In Medicinementioning
confidence: 99%
“…In the pioneering works of Jornet et al [5][6][7], the authors proposed the use of Time-Spread On Off Keying (TS-OOK), where "1" and "0" are represented as a pulse and silence, respectively. Furthermore, a link budget analysis was also presented in [8]. In addition, molecular absorption noise, which is a particular noise that exists when this frequency band is used for communication inside the human body, has been shown to significantly affect the pulses in TS-OOK.…”
Section: Motivationmentioning
confidence: 99%